Bioconversion of Digestate, Pig Manure and Vegetal Residue-Based Waste Operated by Black Soldier Fly Larvae, Hermetia illucens L. (Diptera: Stratiomyidae) - Teun Veldkamp (MDPI AG, 2021)
Insects can play an important role to upgrade waste streams into high-grade proteins and fats as food and feed ingredients or non-food products. The aim of this research was to assess the feasibility to use waste streams with a low value for direct application as animal feed as substrates to grow BSF larvae in terms of larval growth rate, waste reduction index, and efficiency of conversion of ingested feed. The growth of black soldier fly (BSF), Hermetia illucens larvae and conversion of biowaste was assessed in triplicate in biowaste substrates: chicken feed (CF; reference diet), pig manure solid (PMS), Betafert® solid (BTFS), swill (SW), olive pulp (OP), pig manure liquid mixed with chicken feed (PMLCF), and silage grass (SG). Per kilogram fresh substrate 2500 starter (8-days-old, second instar) larvae were incubated in 21 plastic containers (75 × 47 × 15 cm). The BSF larvae were fed according to a batch feeding system. Highest growth rate was found in larvae reared on SW (13.4 mg/d). Larval growth rate was even higher than in larvae reared on the reference substrate CF (7.2 mg/d). Growth rate in larvae reared on PMLCF (7.3 mg/d) did not differ from CF, whereas growth rate of larvae reared on PMS (3.2 mg/d) was lower than on CF. Growth rate of larvae reared on BTFS, OP and SG was very low (0.6, 0.2 and 0.7 mg/d, respectively). Waste Reduction Index (WRI) was highest on SW (11.3), followed by PMLCF (9.3), and both were higher than WRI on CF (8.5). Waste Reduction Index further decreased in descending order from PMS, SG, BTFS to OP (7.6, 4.0, 2.9 and 1.7, respectively). The Efficiency of Conversion of Ingested substrate (ECI) was highest on SW (0.31), followed in descending order by PMLCF, CF and PMS (0.25, 0.21 and 0.18, respectively). The substrates OP, BTFS and SG (0.16, 0.15 and 0.14, respectively) resulted in a lower ECI than other substrates. Highest CO2 and lowest NH3 concentrations were found above substrates with the highest larval growth performances. This study showed that BSF larvae can be reared on different biowaste substrates; the growth rate of the larvae was extremely high on SW. The effects of chemical composition and physical properties of the substrates on larval growth and gas emissions should be further considered.